Assessing the Implementation of total quality management principles on academic achievement of pupils in primary schools in Kenya. - Mukolwe, Joseph Onyango. (JOOUST, 2019)
Despite the presence of management approaches that can be used to enhance academic achievement of pupils, primary schools are faced with the challenge of low academic achievement of pupils in Kenya Certificate of Primary Education. One of the management approaches being used in educational institutions to enhance academic achievement of learners is Total Quality Management (TQM). Total Quality Management is a management approach that was established to seek sources of continuous motion of improvement to provide quality products and hence has become an accepted technique to ensure organizational performance. However, despite the fact that implementation of TQM principles enhances academic achievement, Teso North sub-county is consistently experiencing a challenge of low academic achievement of pupils in KCPE. Therefore, the purpose of this study was to explore the effects of implementation of TQM principles on pupils' academic achievement of pupils in primary schools in Kenya with specific reference to Teso North sub-county. The study focused on four TQM principles namely top management support, teamwork, training, and reward and motivation. This study employed both quantitative and qualitative research methodologies with sequential explanatory research design. Multistage sampling involving purposive, saturated and stratified random techniques were used to select 391 respondents comprising 58 head teachers, 58 deputy head teachers, 436 teachers, drawn from 47 public and 11 private primary schools, the Sub-County Director of Education and Sub-County Quality Assurance and Standard Officer. Questionnaires, interview guides and document analysis were instruments of data collection. The quantitative data were analyzed using descriptive statistics of frequency counts, percentages, means and standard deviations and inferential statistics of Spearman' s rho and linear regression. Qualitative data were analyzed thematically. The findings of this study revealed that each of the TQM principles had a very high and positive statistical significant effect on the academic achievement of pupils. The results further indicated that top management support (B=.879; t = 35.038; p<.05), teamwork (B =.926; t = 24.549; p < .05), training (B =.951; t = 33.595; p < .05) and reward and motivation (B =.829; t = 30.501; p < .05) predicted the academic achievement of pupils. Qualitative data showed Jhat most of the head teachers were not promoting shared academic visions that provided teachers with effective input into academic achievement of pupils and hence the implementation of top management support was largely limited to setting of academic targets without a systematic strategy in place on how to achieve these targets. The data also revealed that there were limited practices of teamwork in primary schools in Teso North sub-county. However, the few schools that fostered teamwork tended to perform better in national examinations. Moreover, the data indicated that Ministry of Education had not yet developed an in-service training policy and this had led to a situation of lack of proper co-ordination and harmonization of the scanty in-service training offered to the primary school teachers. Finally, the qualitative data showed that there were limited avenues for promotion of teachers which had reduced the morale of some teachers thus affecting the quality of their teaching. Therefore, from the findings of this study it was concluded that the TQM principles were essential in predicting academic achievements of pupils. Based on these findings, the study proposed that policy makers at the MOE and the head teachers should formulate strategies for maximizing the influence of implementation of TQM principles for enhancing academic achievement of pupils in primary schools.
Keywords: Total quality management; Implementation of total quality management principles on academic achievement of pupils in primary schools in kenya; Kenya.